IMPLEMENTASI ALGORITMA TANDA TANGAN DIGITAL BERBASIS KRIPTOGRAFI KURVA ELIPTIK DIFFIE-HELLMAN - Asep Saepulrohman; Teguh Puja Negara (Ilmu Komputer, FMIPA, Universitas Pakuan, 2021)
In data communication systems, digital signatures are a form of electronic signature security services based on the Elliptic Curve Digital Signature Algorithm (ECDSA) which are considered resistant to certain types of attacks. Attacks on digital signature schemes aim to fake a signature or are called forgery which is said to be successful if the key pair and signature generated by the attacker are accepted by the verifier. Mathematical schemes used to prove the authenticity of messages or digital documents or guarantees that the data and information actually come from the correct source. ECDSA-based digital signatures rely on discrete logarithmic problems as the basis for mathematical calculations. Q = kP where Q and P are the points of the elliptic curve in the finite field or and k is a positive integer number. The hash function generated from the algorithm process is then encoded (encrypted) with an asymmetric key cryptographic algorithm. In this work use p = 149 to encrypt plain text by converting the original message using dots on a curve with the help of Python programs.